Screening for optimal parameters for modified pharyngeal electrical stimulation for the treatment of dysphagia after stroke in rats - Hu, Jiahui; Wang, Qianqian; Dai, Yong; Tian, Yueqin; Xu, Nenggui; Wen, Hongmei; Dou, Zulin; Ye, Qiuping (Experimental neurology, 2024)
Pharyngeal electrical stimulation (PES), a novel noninvasive peripheral nerve stimulation technique, can effectively improve neurogenic dysphagia and increase the safety and effectiveness of swallowing in the clinic. However, the lack of animal models for dysphagia has limited the mechanistic research on PES, which affects its wide application. Therefore, determining optimal parameters for PES in rats is needed to enable mechanistic studies. Modified PES (mPES), which has different waves and pulse widths from PES, was used; in previous studies mPES was found to have a neurological mechanism like that of PES. A poststroke dysphagia (PSD) model was established, and rats with dysphagia were grouped into three different intensities (0.1 mA, 0.5 mA, and 1 mA) for the selection of optimal intensity and three different frequencies (1 Hz, 2 Hz, and 5 Hz) for the selection of optimal frequency based on a stimulation duration of 10 min in the clinic. A Videofluroscopic Swallow Screen (VFSS) was used to assess swallowing function in rats before and after mPES treatment. The results showed that the 1 mA group had better swallowing function (p < 0.05) than the model group. Compared with the model group, the 1 Hz and 5 Hz groups had the same improvement in swallowing function (p < 0.05). However, the increase in excitatory signals in the sensorimotor cortex was more pronounced in the 5 Hz group than in the other frequency stimulation groups (p < 0.05). Combining the clinical findings with the above results, we concluded that the optimal stimulation parameter for mPES in rats is “frequency: 5 Hz, current intensity: 1 mA for 10 min/day”, which provides a basis for future basic experimental studies of mPES in animals. •mPES was firstly confirmed to improved swallowing function significantly in PSD rats.•1 mA intensity of mPES has more pronounced improvement of swallowing in PSD rats.•1 Hz and 5 Hz frequency of mPES carry out significant effect on swallowing function.•5 Hz frequency of mPES exhibits maximal cortical excitatory activation in PSD rats.•Ischemic stroke rats showed significant swallowing disorders.